(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The ’Stamina case’ raised very sensitive issues concerning the right to health, the limits of therapeutic freedom and the scope of public health policies. Inspired by such case, the contribution aims to reflect on the role played by public institutions in regulating research in that specific area represented by the innovative therapy. In such context, the main topics are the relationship between law and science and the possible conflict between public and individual choices. In particular, the essay examines the way the power to regulate these profiles is shared among public authorities and courts and emphasizes the essential role to be played by the public health administration.